2018
DOI: 10.1177/1369433218782767
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of partly stiffened cold-formed steel built-up beams: Experimental investigation and numerical validation

Abstract: To address the various instability problems in cold-formed steel members, many researchers have mainly focused on developing innovative sectional profiles wherein geometry of the section plays a vital role in enhancing the inherent resistance of such sections against premature buckling. However, the process of forming such innovative shapes is not only complex and time-consuming but sometimes such sections fail to mobilize their complete reserve strength. Hence, a stiffening arrangement of weaker zones for mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Fig. 16 shows the failure mode of the single web beam modeled with the ABAQUS software which was chosen because of its high performance and precision [19][20][21][22]24]. It is noted that the beam I has undergone a local buckling in the upper flange at the level of the zone of application of the load in addition to a distortional lateral buckling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 16 shows the failure mode of the single web beam modeled with the ABAQUS software which was chosen because of its high performance and precision [19][20][21][22]24]. It is noted that the beam I has undergone a local buckling in the upper flange at the level of the zone of application of the load in addition to a distortional lateral buckling.…”
Section: Resultsmentioning
confidence: 99%
“…The basic concept of finite element analysis is that a structure is divided into a finite number of elements having finite dimensions and reducing the structure having infinite degrees of freedom to finite degrees of freedom [18]. For finite element analysis, the advanced ABAQUS software was used for our numerical simulation [2,[19][20][21][22]. The goal of our project is the design of beam models on two supports subjected to bending.…”
Section: Finite Element Modelingmentioning
confidence: 99%
“…Figure 5 shows the semi-log load-displacement trend of HRSTS. At times, the test data may not be clearly interpretable, and semi-log graphs are adopted as a tool of extrapolation (Dar et al , 2019b, 2018b). The peak displacement noted at the other dial gauge location was 46.72 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Open sections from I sections [1,[4][5][6][7], lipped channels [8][9][10][11][12], C sections [2,[13][14][15][16] are presented. Research works of an open section from I section were assembled by screws [4,6,7] and bolts [5].…”
Section: Figure 1 Built-up Open Sectionsmentioning
confidence: 99%
“…Wang and Young [9] investigation showed that design equations were progressive for lipped channels connecting back to back for design strength prediction. Dar et al [10] on doing a study using lipped channel assembled back to back with angle stiffeners found that design strength computed as per North American specification [17]and European Code are conservative. Manikandan and Thulasi [11]on investigating lipped channel stiffened at intermediate web revealed that the provision of intermediate web and edge stiffeners will improve the behaviour and increase the strength of the section.…”
Section: Figure 1 Built-up Open Sectionsmentioning
confidence: 99%